2002
DOI: 10.1007/pl00007113
|View full text |Cite
|
Sign up to set email alerts
|

Kindliche Sehstörungen Screeningprogramme im internationalen Vergleich

Abstract: Worldwide in a number of countries, screening programs aimed at detecting visual disorders in children are established. Repeatedly, proposals are brought forward to optimize already existing programs. Countries without such a program are interested in learning about current models as a guide for planning their own program. This study was performed to take stock of the screening programs for visual dysfunction in children in existence in the years 1999-2000 worldwide. The aspects considered were the child's age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
0
4
0
1
Order By: Relevance
“…Preschool screening programmes for amblyopia were developed in response to experimental data in animals which suggested that early treatment of conditions analogous to human amblyopia is more effective than treatment later in life [ 17 ]. In some countries – for example in Sweden and Israel – these programmes have been well established [ 18 , 19 ]. However, countries like USA, Canada, Belgium and Switzerland have no standardised preschool vision screening programmes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preschool screening programmes for amblyopia were developed in response to experimental data in animals which suggested that early treatment of conditions analogous to human amblyopia is more effective than treatment later in life [ 17 ]. In some countries – for example in Sweden and Israel – these programmes have been well established [ 18 , 19 ]. However, countries like USA, Canada, Belgium and Switzerland have no standardised preschool vision screening programmes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In some countries – for example in Sweden and Israel – these programmes have been well established [ 18 , 19 ]. However, countries like USA, Canada, Belgium and Switzerland have no standardised preschool vision screening programmes [ 19 ]. Although different (cross-sectional) studies, in particular from Scandinavian countries [ 20 ] and a newly released study from Israel [ 18 ], suggest that preschool vision screening is associated with a reduced prevalence rate of amblyopia, the value of these programmes is subject of a continuing scientific and health policy discussion [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Vision screening is predominantly performed by pediatricians, ophthalmologists, and nurses. Other studies confirmed the differences in implementation between countries [14,15]. The representatives of the International Orthoptic Association reported that vision screening was performed by a wide range of professionals [15].…”
Section: Discussionmentioning
confidence: 74%
“…The representatives of the International Orthoptic Association reported that vision screening was performed by a wide range of professionals [15]. Neugebauer et al [14] asked in their study the health ministries of 190 sovereign countries about possibly existing vision screening programs. They found that screening was often state-funded, and within the EU, the screening was predominantly voluntary.…”
Section: Discussionmentioning
confidence: 99%
“…Nach wie vor mangelt es an verbindlichen Empfehlungen, die ein einheitliches Testszenario erlauben. So differieren die Programme in den verschiedenen europäischen Ländern zum Teil erheblich bezüglich verwendeter Tests, Testzeitpunkt und -häufigkeit sowie involvierter Berufsgruppen, Zuweisungsverfahren und Kostenübernahme [5,20,21]. Im Zuge der Analyse der gegenwärtigen Situation in Europa durch die EUS€REEN-Gruppe wurde bereits das Bestreben formuliert, ein optimiertes kosteneffektives Sehscreening unter Berücksichtigung auch spezieller nationaler Gegebenheiten vorzuschlagen [5].…”
Section: Screeninginstitution Und Screeningpopulationunclassified